Research on the Material Removal in the Polishing of Potassium Dihydrogen Phosphate Crystals Based on Deliquescent Action - Shaolong Guo; Feihu Zhang; Yong Zhang; Dianrong Luan (The Scientific World Journal)
Through the polishing experiments of potassium dihydrogen phosphate (KDP) crystals based on deliquescent action, the effect of several major factors, including crystal’s initial surface state, polishing time, and revolution of polishing plate, on material removal was researched. Under certain experimental conditions, the rules of material removal were reached, and experimental results are discussed, which lays the foundation for popularization and application of polishing technology for KDP crystals based on deliquescent action.